Pengaruh Kecerdasan Interpersonal dan Konsistensi Diri terhadap Prestasi Belajar Matematika - Meinar Komala Dewi (Universitas Indraprasta PGRI, 2016)
This research was conducted in Mei 2016. This research is aimed to acknowledging the impacts of interpersonal intelligence and self consistency on mathematical learning achievement. The research was conduted on students X grade in SMA Bunda Kandung. The method used is correlational survey. Population in this research is all students X grade in SMA Bunda Kandung from two class with 48 respondents. The data was taken from even mid test on variables of mathematical learning achievement and questionnaire on variables of interpersonal intelligence and self consistency. Data analyzed used is descriptive statistic analysis and inferensial statistic with double regression. Based on hypothesis analysis on ftest, fcount > ftable. So it can be concluded that there are significant impacts of both interpersonal intelligence and self consistency all together on mathematical learning achievement of the students X grade in SMA Bunda Kandung.